The Role of Ipomea Biloba in Soil Conservation - Naryaana Reddy, B (Journal of Soil and Water Conservation, 2022)
Soil Erosion is a serious problem in all cultivated dry lands. To check this erosion, several states have taken up soil conservation measures. Amon- gest the different soil conservation measures, contour bunding with pro- vision of waste weirs is being exe- cuted on a large scale. Control of gullies in cultivated land is very important as otherwise the gullies slowly cave into the cultivated lands and bodily remove the soil which is lost for ever. The success of contour bunding and gully control measures in soil conservation depends on the rnainte- nance of the bunds and other struc- tures like waste weirs, gully plugs etc, in proper trim. The maintenance of the bunds and other structures is left to the cultivator who, either by ignorance or negligence, is not always alive to the dangers of im- proper maintenance of the structures.